Ecological Education in Everyday Life : ALPHA 2000 - Hautecoeur, Jean-Paul, 1943- (Book collections on Project MUSE., 2002)
Western and Arab researchers look at adult education, and discuss how an ecological approach to education, focussing on the cultural traditions and natural environments of communities, can be more useful than education in specialized institutions.